(untitled) (The Strategic Review for Southern Africa, 2021)
Recent decades have witnessed a ’middle classing of development’ as global institutions hail the expansion of middle classes in the global South. Although the African continent has lagged behind in this regard, expanding middle classes have nonetheless been proclaimed as drivers of development and progress. However, such generalisation smoothes over the rough edges of history, for the emergence, evolution and character of middle classes have been shaped, historically as well as contemporaneously, by the timing and manner of their incorporation into the global system. In this article, it is demonstrated how the character and present prospects of middle classes in key countries in Southern Africa have been differentially shaped, not only by varying experiences under colonial rule, but also by significantly different policies pursued by the party-states of Angola, Mozambique, Zimbabwe and South Africa.